Analisis Pengendalian Persediaan Bahan Baku Menggunakan Metode Economic Order Quality (EOQ) dan Production Order Quantity (POQ) Pada Pabrik Gurilem - Nurfalah; Herdian, Faldy (STIM-LPI Makassar, 2024)
The most important factor that influences a manufacturing company's goals is the smoothness of the production process. The smoothness of the production process is influenced by several factors, one of which is procurement and inventory control of raw materials that will be processed in the production process. Therefore, we need a method that can be used to control raw material supplies. This research uses a quantitative descriptive method because this research relates to a certain period of time by collecting data and information through interviews, observations and documentation related to the company and adjusted to the research objectives. From the results of the research, the EOQ (Economic Order Quantity) and POQ (production order quantity model) methods both have their own effectiveness in inventory control to be applied to companies because purchases based on the EOQ and POQ methods are much more economical than initial factory purchases of Rp. 19,080,000, the EOQ method is IDR 18,809,360 so it can really save inventory costs, especially if the factory uses the POQ method, the company will save even more with inventory costs being IDR 12,858,800 if the company uses this method.